The Motivation Factors Affecting The Performance of The Teacher in Chonburi Primary Educational Service Area office 1 - Taweesup, Sasichaya; Amornkitpinyo, Pimprapa; Amornkitpinyo, Thanyatorn (Journal of Modern Learning Development, 2023)
In this study, the researcher aimed to 1) investigate motivation factors and hygiene factors that affected the performance motivation and encouragement of teacher, 2) to study the relationship between motivation factors, hygiene factors and performance motivation of teacher, and 3) to create equations predicting teacher’s performance motivation. This research was a Quantitative Research. The population consisted of 794 teacher and the samples used in this research are 300 government primary school teachers in Chonburi primary educational service area office 1. The implemented data collection method is questionnaire. The presented statistical indexes are mean), standard deviation (S.D.), Pearson’s Product Moment Correlation Coefficient, and Stepwise Multiple Regression Analysis. The findings revealed that the variable that affected teacher’s performance motivation the most was ‘performance success’ ( = 4.47, S.D. = .50), whereas the least affected variable was ‘compensation’ ( = 4.22, S.D. = .84). and the mean of teacher’s performance motivation was ( = 4.49, S.D. = .52). In addition, there were 10 variables that were related to performance motivation of teachers; 1) performance success (), 2) respect and admiration (), 3) task characteristics (), 4) responsibility (), 5) opportunity to be promoted (), 6) compensation (), 7) interpersonal relationship (), 8) policy and management (), 9) work environment (), and 10) job stability (). All of The 55 pairs of teacher’s performance motivation (Y) were between .542 - .795 with the significance level of .05. The result of stepwise multiple regression analysis implied that there were 4 factors performance success (), task characteristics (), interpersonal relationship (), and work environment () that could explain the variance of teacher’s performance motivation at 68 percent. The predictive equations in unstandardized and standardized scores are as follows: The Predictive Equation in Unstandardized score: = .775 + .201 + .319 + .153 + .165 The Predictive Equation in Standardized score: = .192 + .360 + .185 + .220